Evaluating the Implementation of Konawe's Traditional Attire Regulation Using the CIPP Model - Ramadhan Tosepu; Guswan Hakim; Danial; Fitrah Asfian (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The preservation of local culture is an important aspect of regional development, especially in the era of globalization that tends to marginalize traditional values. One of the strategic steps taken by the Konawe Regency Government is the issuance of Regional Regulation Number 18 of 2018 concerning Official Traditional Attire of Konawe Regency Objectives: This study aims to analyze the content and implementation of the regional regulation by examining its relevance, objectives, supporting resources, implementation process, and its social and economic impacts on the community. Methods: This research uses a descriptive method with a policy review approach. Data were collected through document analysis. Results: The findings show that the regulation is relevant to the need to preserve the Tolaki traditional attire as a local identity. However, its implementation still faces challenges, such as limited socialization, lack of supporting resources, and the absence of clear monitoring mechanisms. Despite these challenges, the policy has had a positive impact on cultural strengthening and the development of creative industries among local artisans. Conclusion: The study concludes that continuous evaluation is needed to optimize the impact of the regulation on cultural sustainability and regional development.